Determinants of Intrauterine Contraceptive Device Use Among the Women of Urban Areas of Nepal - Joshi, R; Bhattarai, S; Simkhada, K; Thapa, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study aimed to identify the determinants of Intrauterine Contraceptive Device (IUCD) use among the married women of reproductive age group living in urban areas of Nepal. Methods: This study was an analytical cross-sectional study which aimed to compare different factors between 110 IUCD users and 110 non-users. Both groups were selected randomlyand interviewed by using semi-structured questionnaire. Chi-square test was used to detect the difference between two groups and corresponding odds ratios with 95% confidence intervals were also computed. Results: When the IUCD users were compared to non-users, religion, occupational status of women, occupational status of the husbands, total number of children, sources of information about IUCD, having wrong beliefs about IUCD, availability of IUCD services, reproductive intention and spousal communication were significantly associated with the use of IUCD.The main reason for using IUCD was due to the effectiveness for longer duration and for not using IUCD was due to the feeling of no need. Conclusions: Wrong beliefs about the device discouraged women from using IUCD, hence, awareness programs are strongly recommended. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 16-20 DOI: http://dx.doi.org/10.3126/njog.v8i2.9760